Role of Lipid Rafts on LRP8 Signaling Triggered by Anti-β2-GPI Antibodies in Endothelial Cells - Gloria Riitano; Antonella Capozzi; Serena Recalchi; Mariaconcetta Augusto; Fabrizio Conti; Roberta Misasi; Tina Garofalo; Maurizio Sorice; Valeria Manganelli (Biomedicines, 2023)
Antiphospholipid antibody syndrome is an autoimmune disease characterized by thrombosis and/or pregnancy morbidity in association with circulating antiphospholipid antibodies, mainly anti-β2 glycoprotein 1 antibodies (anti-β2-GPI antibodies). Previous studies demonstrated that the signaling pathway may involve lipid rafts, plasma membrane microdomains enriched in glycosphingolipid and cholesterol. In this study, we analyzed the signaling pathway of LRP8/ApoER2, a putative receptor of anti-β2-GPI antibodies, through lipid rafts in human endothelial cells. LRP8, Dab2 and endothelial nitric oxide synthase (e-NOS) phosphorylation were evaluated using Western blot, Nitric Oxide (NO) production with cytofluorimetric analysis, LRP8 enrichment in lipid rafts via sucrose gradient fractionation, and scanning confocal microscopy analysis of its association with ganglioside GM1 was also conducted. The analyses demonstrated that affinity-purified anti-β2-GPI antibodies induced LRP8 and Dab-2 phosphorylation, together with a significant decrease in e-NOS phosphorylation, with consequent decrease in NO intracellular production. These effects were almost completely prevented by Methyl-β-cyclodextrin (MβCD), indicating the involvement of lipid rafts. It was supported with the observation of LRP8 enrichment in lipid raft fractions and its association with ganglioside GM1, detected with scanning confocal microscopy. These findings demonstrate that LRP8 signaling triggered by anti-β2-GPI antibodies in endothelial cells occurs through lipid rafts. It represents a new task for valuable therapeutic approaches, such as raft-targeted therapy, including cyclodextrins and statins.